Understanding the influence of personality traits on psychological well-being: A study of caregivers of children with autism spectrum disorder - Napitupulu, Lisfarika; Razak, Ateerah Abdul; Kurniawan, Yohan; Fadhlia, Tengku Nila; Arief, Yanwar; Nugroho, Sigit (Faculty of Psychology and Health - Universitas Islam Negeri Walisongo Semarang, 2023)
Caregivers of children with autism spectrum disorder experience psychological pressure, which can affect their psychological well-being. This study aims to identify the personality traits which influence such well-being. A quantitative method was employed, involving 213 Indonesian participants who were caregivers of children with autism attending special schools or enrolled at specialized therapy centers, selected through purposive sampling. The personality traits were measured using the IPIP-BFM-25 scale, while psychological well-being was assessed using the Psychological Well-Being Scale. The data were analyzed using the PLS-SEM method with SMART PLS 3.0 software, employing the disjoint two-stage estimation approach. The results show that the traits of extroversion (β = 0.222, t = 2.249, p = .021); conscientiousness (β = 0.258, t = 2.782, p = .003); and emotional stability (β = 0.302, t = 4.371, p = .000) positively affected the caregivers’ psychological well-being. However, those of agreeableness and intellect did not have a significant impact. It is hoped that the study findings will contribute to the efforts to enhance the mental health of caregivers of children with autism.